Hematological features of mine-blast trauma, accompanied by acubarotrauma, among servicemen - participants in high-intensity combat operations - S. A. Husieva; G. V. Osyodlo; I. P. Goncharov; O. Ya. Antonyuk; Yu. Ya. Kotyk; A. V. Gusev; М. Е. Krol; I. V. Malysh; Ya. M. Klimenko; S. V. Ткаchenko (Український журнал військової медицини)
During the full-scale war in Ukraine, the number of military personnel sufferinged from mine-blast trauma (MBT) significantly increased. The work aimed to generalise and study the clinical and hematological characteristics of service members who received MBT during combat operations.